VARIETAS BERAT SAMPEL BATUBARA UNTUK PENGEMBANGAN METODE UJI TOTAL SULFUR DENGAN STANDAR ASTM D4239-18E1 MENGGUNAKAN SULFUR ANALYZER - Yeheskiel Yunus Buttu; Abelina Aprilyantin Ekasari Utami; Vrederix Dandy (Prodi Teknik Kimia, 2023)
Coal is an organic rock that has a high selling value because it is capable of producing energy into fuel, and is currently still needed by industries that use dry fuel. Coal is obtained from mining companies in Indonesia. In detail, most coal in Indonesia is obtained from the provinces of East Kalimantan and South Kalimantan. Coal contains many elements of carbon, nitrogen, hydrogen and a little sulfur. Each coal mining company will have different coal quality, so coal quality needs to be determined according to testing standards. Total sulfur is one of the test parameters in coal before it is used. The purpose of this research is to determine the total sulfur value of coal by varying the sample weight. The variety of weights used for the development of the total sulfur analysis method for coal samples, can be seen the range of sample weights used for the total sulfur test for coal samples with the ASTM D4239-18E1 standard. Coal sample test method used with a weight variety of 0.0500 gram; 0.1000 grams; 0.1500 grams; 0.2000 grams; 0.2500 grams; and 0.3000 grams. Sulfur analyzer is used at a temperature of 1350 ̊C because it involves a combustion process. The burning coal sample will decompose into sulfur oxide compounds which will be detected by an infrared detector. Oxygen gas with a purity of 99.5% is used to burn the coal sample. Coal sample weight with constant reading results obtained at a sample weight of 0.2000 grams to 0.3000 grams.